The intellectual lives of children - Engel, Susan L., 1959- (Harvard University Press, 2021)
"Susan Engel has spent her career observing and interacting with children as they learn. Drawing on a wealth of research-her own and others'-Engel shows parents and teachers how they can better nurture the intellectual lives of kids by recognizing learning that might go unnoticed and by creatively encouraging curiosity and problem solving"--